Vulvovaginal Reconstruction With a Modified Pedicled Anterolateral Thigh Flap - Akatsuki Kondo, MD, PhD; Hiroki Umezawa, MD, PhD; Marie Taga, MD; Rei Ogawa, MD, PhD, FACS (Plastic and Reconstructive Surgery, Global Open)
Summary:. This case report presents a novel approach for vulvovaginal reconstruction using a modified pedicled anterolateral thigh (ALT) flap. The patient was a 62-year-old woman with a history of vulvar squamous cell carcinoma and radiation therapy, after which the cancer recurred. Total vulvectomy was performed with preservation of the urethra and vaginal introitus. The resulting defect was reconstructed using a boomerang-shaped ALT flap measuring 16 × 7 cm. The flap was harvested via intramuscular dissection and transposed into the vulvar defect through a subcutaneous tunnel. The excess skin was de-epithelialized and used to fill the defect around the urethra. Six months postoperatively, the patient had recovered successfully with satisfactory cosmetic and functional results. The advantages of the ALT flap include its versatility, long vascular pedicle, and the ability to harvest it from a nonirradiated area. The modified technique used a boomerang-shaped design and careful placement of the perforators. This technique eliminates the disadvantages associated with fenestrated and split ALT flaps, provides well-vascularized tissue, restores function, minimizes donor-site morbidity, and achieves a natural-looking aesthetic result. The modified pedicled ALT flap is a safe and effective method for vulvovaginal reconstruction, particularly in patients with a history of radiation therapy or large, complex vulvar defects.